Relative and absolute within-session reliability of the modified Star Excursion Balance Test in healthy elite athletes - Onofrei, R. R.; Amaricai, E.; Petroman, R.; Suciu, O. (PeerJ, 2019)
Background: The Star Excursion Balance Test (SEBT) is commonly used to assess dynamic postural balance both in clinical practice and research. The aim of our study was to assess the within-session relative and absolute reliability of participants` performance of the modified SEBT (mSEBT) using a single practice trial in healthy elite athletes who were familiar with the test. Methods: An intra-session repeated-measures design was used to investigate the relative and absolute reliability of participants` (healthy athletes partaking in sports at a high-risk of ankle sprain injury) performance of the mSEBT. A total of 122 healthy elite athletes from soccer (n = 73), basketball (n = 15), and volleyball (n = 34) performed one practice trial and three test trials within one session, in three directions (anterior, postero-medial, and postero-lateral), for both legs. Intraclass correlation coefficient (ICC), standard error of measurement (SEM), and smallest detectable change at a 95% confidence were calculated. Results: We found a good to excellent relative within-session intra-rater reliability between the three trials on specified directions, with an ICC (3,1) from 0.90 to 0.95. SEM and SDC95 for normalized and composite scores, for both legs ranged from 0.91 to 2.86, and 2.54 to 7.94, respectively. Conclusions: In conclusion, we report good to excellent within-session reliability for the mSEBT. Our results confirm that the test can be reliably used with only one practice trial in healthy elite athletes familiar with the test.